Pengaruh Kadar Gula Darah terhadap Hipertensi di RSUD Rantauprapat - Uli Syahri Rizki; Zata Ismah; Reni Agustina; Wasiyem Wasiyem; Hery Sahputra (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: T2DM is a background for other diseases, one of which is hypertension. Hypertension can be triggered from T2DM through the mechanism of insulin resistance which then causes hyperinsulinemia, dyslipidemia, and hyperglycemia. The purpose of this study was to determine the effect of blood sugar levels on hypertension in patients with type 2 diabetes mellitus at RSUD Rantauprapat.Methods: Quantitative research with an analytic cross-sectional approach conducted in December 2022-June 2023. There were 205 respondents aged 20-79 years who were taken through simple random sampling. Using data collection sheet instruments. With the analysis used is Univariate, bivariate (Chi-square), and Confounding Mantel Haenszel.Results: Chi-square analysis states that blood sugar levels are significantly associated with hypertension with OR 10.800 (95%CI: 5.410-21.560). Where the confounding analysis of Mantel Haenszel age, gender and occupation are confounding factors that affect blood sugar levels and hypertension with risk difference (OR>10%).Conclusion: The study states that there is an influence between blood sugar levels and hypertension. The government is expected to provide education to change the patient's unhealthy lifestyle so as not to lead to other complications.